Refractory hyperglycemia in a geriatric patient with diabetic ketoacidosis: A critical care nursing case report - Yodha Pranata; Winara Winara; Intan Rizkianti; Nina Maryam; Ayu Prawesti (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Refractory hyperglycemia in diabetic ketoacidosis (DKA) presents a critical challenge in geriatric patients due to multifactorial physiological and clinical complexities. Early recognition and integrated management are essential, with critical care nursing as a pivotal component. Purpose: This case report aims to describe and analyze the multifactorial causes of refractory hyperglycemia in a geriatric DKA patient, highlighting the importance of early detection, comprehensive correction, and collaborative nursing roles. Method: A descriptive analytic approach was employed to examine the clinical course of a 75-year-old woman with DKA and persistent hyperglycemia. Data were collected from direct patient observation, systematic physical examinations, laboratory assessments, imaging, and multidisciplinary clinical records. Daily therapeutic interventions and patient responses were meticulously documented. Results: Persistent hyperglycemia resulted from several interacting factors: the impact of glucocorticoids on glycemic control, effects of severe pulmonary infection on insulin resistance, the role of electrolyte disturbances in exacerbating hyperglycemia, the relationship between heart failure and diuretic use, the impact of malnutrition and sarcopenia on insulin resistance, and the need for an integrated therapeutic approach. Each factor contributed to increased insulin resistance and complicated glycemic control. Conclusion: Optimal management of refractory hyperglycemia in elderly DKA patients requires early identification and simultaneous correction of underlying factors, supported by intensive critical care nursing and multidisciplinary collaboration.